Early life height and weight production functions with endogenous energy and protein inputs - Puentes, Esteban; Wang, Fan; Behrman, Jere R.; Cunha, Flavio; Hoddinott, John F.; Maluccio, John A.; Adair, Linda S.; Borja, Judith B.; Martorell, Reynaldo; Stein, Aryeh D. (Elsevier, 2016)
We examine effects of protein and energy intakes on height and weight growth for children between 6 and 24 months old in Guatemala and the Philippines. Using instrumental variables to control for endogeneity and estimating multiple specifications, we find that protein intake plays an important and positive role in height and weight growth in the 6-24 month period. Energy from other macronutrients, however, does not have a robust relation with these two anthropometric measures. Our estimates indicate that in contexts with substantial child undernutrition, increases in protein-rich food intake in the first 24 months can have important growth effects, which previous studies indicate are related significantly to a range of outcomes over the life cycle.